Quality care for children and young people with complex and integrated care needs: A discussion on nursing-sensitive indicators - Rosemarie Sheehan; Mary Ryder; Maria Brenner (International Journal of Nursing Studies Advances)
This paper highlights the need for nursing-sensitive indicators tailored to children and young people with complex and integrated care needs. While nursing plays a pivotal role in influencing care quality for this population, current measures predominantly focus on adult populations, creating gaps that hinder the evaluation of nursing contributions across diverse settings such as acute, community, and home care. We examine the importance of quality care measurement for children and young people with complex and integrated care needs and highlight deficiencies in international measurement systems. The discussion highlights the multidimensional care needs of this vulnerable population and advocates for nursing-sensitive indicators that capture broader outcomes including physical health, functional outcomes, family experience, and family well-being. Also highlighted is, the weak evidence linking process indicators to improved patient outcomes, a focus on negative outcomes, such as mortality, and the lack of theoretical foundations for nursing-sensitive indicators. There is a lack of consensus on what components to measure, definitions of indicators, and appropriate methodologies for the development of nursing sensitive indicators. Donabedian's (1988) structures, processes, and outcomes framework is discussed as well as an overview of adaptations used to improve the quality of indicator sets in a variety of settings. By situating the discussion within the context of children's and young people's nursing, this paper aims to direct future research towards the development of comprehensive indicators that capture the full contribution of nursing to the care of children and young people with complex and integrated care needs. Ultimately, this paper advocates for a standardised, holistic approach to nursing-sensitive indicators for this vulnerable population to improve care quality and overall health and wellbeing for children, young people, and their families.